Measuring ideas of persecution and social reference: the Green et al. Paranoid Thought Scales (GPTS). - Green, C; Freeman, D; Kuipers, E; Bebbington, P; Fowler, D; Dunn, G; Garety, P (2008)
BACKGROUND: Paranoia is increasingly being studied in clinical and non-clinical populations. However there is no multi-dimensional measure of persecutory ideas developed for use across the general population-psychopathology continuum. This paper reports the development of such a questionnaire: the 'Green et al. Paranoid Thought Scales'. The aim was to devise a tool to assess ideas of persecution and social reference in a simple self-report format, guided by a current definition of persecutory ideation, and incorporating assessment of conviction, preoccupation and distress. METHOD: A total of 353 individuals without a history of mental illness, and 50 individuals with current persecutory delusions completed a pool of paranoid items and additional measures to assess validity. Items were devised from a recent definition of persecutory delusions, current assessments of paranoia, the authors' clinical experience, and incorporated dimensions of conviction, preoccupation and distress. Test-retest reliability in the non-clinical group was assessed at 2 weeks follow-up, and clinical change in the deluded group at 6 months follow-up. RESULTS: Two 16-item scales were extracted, assessing ideas of social reference and persecution. Good internal consistency and validity was established for both scales and their dimensions. The scales were sensitive to clinical change. A hierarchical relationship between social reference and persecution was found. The data provide further evidence for a continuum of paranoid ideas between deluded and healthy individuals. CONCLUSIONS: A reliable and valid tool for assessing paranoid thoughts is presented. It will provide an effective way for researchers to ensure consistency in research and for clinicians to assess change with treatment.